Validation of remote digital frozen sections for cancer and transplant intraoperative services - Luca Cima; Matteo Brunelli; Anil Parwani; Ilaria Girolami; Andrea Ciangherotti; Giulio Riva; Luca Novelli; Francesca Vanzo; Alessandro Sorio; Vito Cirielli; Mattia Barbareschi; Antonietta D'Errico; et al. (Elsevier, 2018)
Introduction: Whole-slide imaging (WSI) technology can be used for primary diagnosis and consultation, including intraoperative (IO) frozen section (FS). We aimed to implement and validate a digital system for the FS evaluation of cancer and transplant specimens following recommendations of the College of American Pathologists. Materials and Methods: FS cases were routinely scanned at ×20 employing the "Navigo" scanner system. IO diagnoses using glass versus digital slides after a 3-week washout period were recorded. Intraobserver concordance was evaluated using accuracy rate and kappa statistics. Feasibility of WSI diagnoses was assessed by the way of sensitivity, specificity, as well as positive and negative predictive values. Participants also completed a survey denoting scan time, time spent viewing cases, preference for glass versus WSI, image quality, interface experience, and any problems encountered. Results: Of the 125 cases submitted, 121 (436 slides) were successfully scanned including 93 oncological and 28 donor-organ FS biopsies. Four cases were excluded because of failed digitalization due to scanning problems or sample preparation artifacts. Full agreement between glass and digital-slide diagnosis was obtained in 90 of 93 (97%, κ = 0.96) oncology and in 24 of 28 (86%, κ = 0.91) transplant cases. There were two major and one minor discrepancy for cancer cases (sensitivity 100%, specificity 96%) and two major and two minor disagreements for transplant cases (sensitivity 96%, specificity 75%). Average scan and viewing/reporting time were 12 and 3 min for cancer cases, compared to 18 and 5 min for transplant cases. A high diagnostic comfort level among pathologists emerged from the survey. Conclusions: These data demonstrate that the "Navigo" digital WSI system can reliably support an IO FS service involving complicated cancer and transplant cases.